Municipal waste management performance: a focus on Slovakia and its LAU-1 districts - Eleonóra Marišová; Peter Fandel (Acta Polytechnica CTU Proceedings)
In this paper, we analyse the changes made to the basic EU directive on waste and assess its impact on the waste legislation of EU members. We then examine the Slovak waste strategies/programs that have implemented the EU directive on waste, namely the Waste Prevention Program, the Waste Management Program, and the Envirostrategy 2030. Based on EU waste legislation, the Environmental Strategy 2030 sets the waste treatment aims for Slovakia until 2030. However, it is questionable whether Slovakia will achieve the set goals. Our research indicates that as of 2021, Slovakia’s rate of waste incineration with energy recovery and landfilling rate of municipal waste are below the EU average, while the recycling rate, both for materials and composting and digestion, is higher. In our quantitative analysis, we examine the progress of waste management performance in Slovakia from 2017 to 2021, focusing on the LAU-1 districts. We estimate composite efficiency indicators using the techniques of Data Envelopment Analysis and Malmquist Indices. In accordance with the hierarchy of waste treatment methods, the applied models consider desirable waste operations variables (recycling and incineration with energy recovery) and undesirable waste operation variables (landfilling). Our results reveal significant variations in efficiency across the LAU-1 districts. The average technical efficiency of the 72 districts has improved from 0.714 in 2017 to 0.852 in 2021, indicating that the performance of districts is generally improving and catching up with the best-performing districts. The total performance, as measured by the Malmquist index, has improved by 45.5 %. Districts with access to waste incineration facilities with energy recovery have exhibited higher efficiency scores, benefitting from this advantage.